Clinical Functional MRI Presurgical Functional Neuroimaging - Stippich, Christoph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Functional magnetic resonance imaging (fMRI) has contributed significantly to progress in neuroscience by permitting noninvasive imaging of the "human brain at work" under physiological conditions. Within clinical neuroimaging, fMRI is opening up a new diagnostic field by measuring and visualizing brain function. However, fMRI is not yet a standard diagnostic imaging procedure. This textbook is devoted to preoperative fMRI in patients with brain tumors and epilepsies, which are the most well-established clinical applications. By localizing and lateralizing specific brain functions in individual patients, as well as epileptogenic zones, fMRI facilitates the selection of a safe treatment and the planning and performance of function-preserving neurosurgery. State of the art fMRI procedures are presented, with detailed consideration of practical aspects, imaging and data processing, normal and pathological findings, and diagnostic possibilities and limitations. The relevant information on brain physiology, functional neuroanatomy, imaging technique, and methodology is provided by recognized experts in these fields. Further chapters address the validity of presurgical functional localization, multimodality functional neuroimaging, brain plasticity, and pitfalls, tips, and tricks. The book is designed to be of value to beginners, trained clinicians and experts alike.
to Presurgical Functional MRI -- Localization of Brain Activity using Functional Magnetic Resonance Imaging -- Functional Neuroanatomy -- Presurgical Functional MRI in Patients with Brain Tumors -- Presurgical Functional MRI in Epilepsy -- Functional Neuronavigation -- Validity of Presurgical Functional Localization -- Multimodality in Functional Neuroimaging -- Brain Plasticity and fMRI -- Clinical BOLD fMRI: Artifacts, Tips and Tricks.
Keywords: Neurology .; Radiology; Neuroradiology; Neurosurgery; Radiotherapy; Neurology; Imaging / Radiology; Diagnostic Radiology; Neuroradiology; Neurosurgery; Radiotherapy